2016
DOI: 10.3892/mmr.2016.5710
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Ciwujianoside C3, extracted from the leaves of Acanthopanax henryi (Oliv.) Harms, on LPS-stimulated RAW 264.7 cells

Abstract: The present study aimed to investigate the unknown mechanisms underlying the anti‑inflammatory activity of Ciwujianoside C3 (CJS C3), extracted from the leaves of Acanthopanax henryi Harms, on lipopolysaccharide (LPS)‑stimulated RAW 264.7 cells. Cells were treated with CJS C3 for 1 h prior to the addition of 200 ng/ml LPS. Cell viability was measured using the MTS assay. Nitric oxide levels were determined by Griess assay. Proinflammatory cytokine production was measured by enzyme‑linked immunosorbent assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…For example, a hydrophilic compound, morphine-6-glucuronide are considered to be actively transported in the brain by unknown transporter [20]. There might be something transport system for ciwujianoside C3, eleutheroside M and ciwujianoside B. Pharmacological effects of ciwujianoside C3, eleutheroside M and ciwujianoside B were hardly reported except for following two reports using damaged cell conditions; ciwujianoside C3 inhibits proinflammatory cytokine levels in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells [21], ciwujianoside B reduces DNA damage in bone marrow cells exposed to radiation [22]. No studies reported effects of these three compounds on neuronal function in healthy condition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a hydrophilic compound, morphine-6-glucuronide are considered to be actively transported in the brain by unknown transporter [20]. There might be something transport system for ciwujianoside C3, eleutheroside M and ciwujianoside B. Pharmacological effects of ciwujianoside C3, eleutheroside M and ciwujianoside B were hardly reported except for following two reports using damaged cell conditions; ciwujianoside C3 inhibits proinflammatory cytokine levels in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells [21], ciwujianoside B reduces DNA damage in bone marrow cells exposed to radiation [22]. No studies reported effects of these three compounds on neuronal function in healthy condition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that this plant exhibits diverse pharmacological activities due to the wide variety of chemical constituents. For example, metabolites of the leaves of A. henryi have strong antioxidant and antiacetyl cholinesterase activities [6], and the 80% methanol fraction of root bark and ciwujianoside C3, which was isolated from leaves of this plant, have significant anti-inflammatory effect in lipopolysaccharide- (LPS-) induced RAW264.7 macrophage cells [5, 11]. Moreover, some glycosides from the leaves of A. henryi have antiadipogenic effect, decreasing lipid accumulation through the inhibition of proliferator-activated receptor gamma (PPAR γ ) and CCAAT/enhancer-binding protein alpha (C/EBP α ) in 3T3-L1 cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HMGB1 is an important ligand of TLR4 that induces the release of proinflammatory cytokines (55,56). HMGB1-TLR4 signaling induces the activation of MAPK and NF-κB (57), and the activation of NF-κB leads to the increased release of various proinflammatory cytokines, including IL-1β, IL-6 and TNF-α (5860). The release of proinflammatory cytokines can lead to the recruitment of inflammatory cells into the pulmonary microvasculature (61,62).…”
Section: Discussionmentioning
confidence: 99%